Gongronella fusoacuminata (Cunninghamellaceae, Mucorales), a new species from Taiwan - Wei, Yu-Hui; Liou, Guey-Yuh; Tzean, Shean-Shong; Hsieh, Sung-Yuan (Phytotaxa, 2024)
Rhizosphere fungi play crucial roles in plant health and soil ecology. We describe and illustrate Gongronella fusoacuminata, a new species isolated from the rhizosphere soil of pine and mallow in Taiwan. Phylogenetic analyses based on both ITS and LSU rDNA sequences, in conjunction with unique morphological characteristics, confirmed its distinct taxonomic classification within the genus. The phylogenetic analyses revealed that G. fusoacuminata possesses distinctive sequences, clearly differentiating it from other species within the genus. In addition, G. fusoacuminata is distinguished by its fusiform sporangiospores with acuminate apices and their relatively large size, clearly discerning it from other documented species.